Investigating the Relationship among Stability Indices with Severity of Pain, Disability and Duration of Disease in People with Cervicogenic Headache - Miri, Mahnaze; Akbari, Mohammad; Abaspour, Omolbanin; Dadgoo, Mehdi (Journal of Clinical Physiotherapy Research, 2018)
Introduction: Cervicogenic headache is a secondary headache, whose cervicogenic disorders is known as its background factor. Considering the important role of cervical spine in providing deep-feeling entrances, a change in deep-feeling entrances can lead to disorder in these individuals. The aim of this study was to investigate the relationship between stability and severity of pain, disability and duration of headache in these patients. Methodology: In this cross-sectional study, 30 cervicogenic patients, headache index, duration of illness, disability inventory and visual acuity scale were recorded. To measure the stability, stability tests were performed in four standing positions on two extremities with open and closed eyes and with low and high stability level by Biodex stability device. The overall stability index, internal-external index and anterior-posterior index were measured. Pearson correlation test was used to examine the relationship between variables. Results: There was a significant relationship between the history of headache reporting and most of the stability indices (p=0.002, r=0.548). There was a significant relationship between the general stability index (p=0.001, r=0.563) and internal-external index and pain severity, and no significant correlation was found between the anterior-posterior index. There was no significant relationship between disability inventory (p=0.727) and headache index (p=0.186) with stability indices. Conclusion: With increasing duration of headache and increased pain intensity, stability indices increase, which can indicate a weaker stability in cervicogenic headache patients with longer illness history and more pain intensity. Keywords: Biodex Stability Device, Cervicogenic Headache, Disability, Duration Of Illness, Pain, Stability